2D Graphitic Carbon Nitride for Energy Conversion and Storage. (19th June 2021) - Wang, Yinghui; Liu, Lizhen; Ma, Tianyi; Zhang, Yihe; Huang, Hongwei
Abstract: Graphitic carbon nitride (g‐C3 N4 ) have attracted great attention in the field of energy conversion and storage due to its unique layered structure, tunable bandgap, metal‐free characteristic, high physicochemical stability, and easy accessibility. 2D g‐C3 N4 nanosheets have the features of short charge/mass transfer path, abundant reactive sites and easy functionalization, which are beneficial to optimizing their performance in different fields. However, the reviews of the comprehensive applications of 2D g‐C3 N4 for energy conversion and storage are rare. Herein, this review first introduces the physicochemical properties of bulk g‐C3 N4 and g‐C3 N4 nanosheets, and then summarizes the synthetic strategies of 2D g‐C3 N4 nanosheets in detail, such as thermal oxidation etching, chemical exfoliation, ultrasonication‐assisted liquid phase exfoliation, chemical vapor deposition, and others. Emphasis is focused on the rational design and development of 2D g‐C3 N4 nanosheets for the diversified applications in energy conversion and storage, including photocatalytic H2 evolution, CO2 reduction, electrocatalytic H2 evolution, O2 evolution, O2 reduction, alkali‐metal ion batteries, lithium‐metal batteries, lithium–sulfur batteries, metal‐air batteries, and supercapacitors. Finally, the current challenges and perspectives of 2D g‐C3 N4 nanosheets for energy conversion and storage applications are discussed. Abstract : 2D g‐C3 N4 features a short charge/mass transfer path, abundant reactive sites, and easy functionalization, which are promising for energy conversion and storage. Based on the inherent properties and structural advantages of 2D g‐C3 N4, the advancements in the diverse applications of 2D g‐C3 N4 in photocatalysis, electrocatalysis, batteries, and supercapacitors are elaborately summarized.